catena-Poly[[(tetrahydrofuran-κO)lithium(I)]-bis(μ-trimethylsilanolato-κ(2) O:O)-gallium(III)-bis(μ-trimethylsilanolato-κ(2) O:O)-[(tetrahydrofuran-κO)lithium(I)]-μ-bromido] - Grubba, Rafał (International Union of Crystallography, 2010)
The title chain polymer compound, [GaLi(2)Br(C(3)H(9)OSi)(4)(C(4)H(8)O)(2)](n), was obtained in the reaction of GaBr(3) with Me(3)SiOLi in toluene/tetrahydrofuran. The Ga(III) atom, located on a twofold rotation axis, is coordinated by four trimethylsilanolate ligands and has a distorted tetrahedral geometry. The Li(I) atom is four coordinated by one bridging Br atom located on an inversion centre, two trimethylsilanolate ligands and one tetrahydrofurane molecule in a distorted tetrahedral geometry. The polymeric chains extend along [001]. The tetrahydrofurane molecule is disordered over two positions with site-occupancy factors of 0.57 (2) and 0.43 (2).